Estudos sobre a epidemiologia da doença de Chagas no Ceará XX - ecologia de triatomíneos em russas - Joaquim Eduardo de Alencar; Otávio Ferreira Bezerra; Oswaldo Freire de Faria Filho (Revista da Sociedade Brasileira de Medicina Tropical, 1982)
Foi escolhida para demolição, no Município de Russas, território do Triatoma braziliensis, uma casa borrifada 104 dias antes com BHC. Na área - a Fazenda Boa Vista - resisdem 250 habitantes; a taxa de infecção humana é 7,7% (imunofluorescência indireta) e a de cães é 9,1% (xeno). A captura prévia na área revelou 171 T. braziliensis (46,8%) infectados e raros Triatoma pseudo maculata (5). Na casa havia um habitante com teste de imunofluorescência positivo e de 26 T. braziliensis capturados nenhum revelou infecção. Durante a demolição foram capturados 1 rato infectado pelo Trypanosoma cruzi e 104 triatomíneos, (89,4% T. pseudomaculata e 10,6% T. brazieliensis); havia R. nasutus infectado no galinheiro. Exemplares de T. pseudomaculata infectados foram encontrados no teto 10,6 por m²) e nas paredes externas e internas da sala (0,8 por m²); ao teste de precipitina revelaram acentuada antropofilia. Concluiu-se que numa casa normalmente habitada por T. braziliensis, após a borrifação, houve substituição dessa espécie por uma população de T. pseudomaculata, numa área com razoável antropofilia e taxa de infecção suficiente para a transmissão. A house sprayed 104 days before with BHC was selected for demolition. It was sited in the municipality of Russas, an endemic area of Triatoma braziliensis, in the farm of Boa Vista. Bug capture in the area revealed that of 171 T. braziliensis 48.8% were infected with Trypanosoma cruzi. Only five Triatoma pseudo maculata were caught. Of the 250 inhabitants of this farm 7.7% had positive serology for T. cruzi infection (indirect immunofluorescent test). 9.1% of dogs had positive xenodiagnoses. In the house to be demolished one inhabitant had positive serology but 26 T. braziliensis captured before dmolition were all uninfected. During demolition an rat infected with T. cruzi was found and of 104 triatomine bugs 89.4% were T. pseudomaculata and 10.6% T. braziliensis. Infected Rhodnius nasutus was found in the chicken house. Examples of T. pseudomaculata were found in the roof (0.6 per swquare metrejand in the external an internal walls of the living room (0.8 per square metre). Precipitin tests of blood meals revealed marked anthrophilia. We believe this house to have been initially colonised by T. braziliensis. After sprying this species was substituted by T. pseudomaculata a species feeding on man with a infection rate sufficient to effect transmission.